Pyrrhonism, inquiry, and rationality - Machuca, Diego Emanuel (2013)
This paper offers a detailed examination of the Skeptic´s philosophical investigation and his attitude towards the requirements of rationality. In so doing, it engages with the interpretation advanced by Casey Perin in his recent book: The Demands of Reason: An Essay on Pyrrhonian Scepticism (OUP, 2010).